Integration of Community Strategies and Community Nurse Interventions in Health Crisis Handling Health Sociology Approach - Baso Witman Adiaksa; Muhammad Ilyas (JAKESPOL Journal of Health Policy Analysis, 2026)
Introduction: Health crises require adaptive, socially grounded responses that integrate formal health systems with community capacity. In Makassar, Indonesia, disparities in access, social heterogeneity, and varying levels of health literacy intensify vulnerability during crises. This study aimed to develop and examine an integrative model combining community strategies and community nurse interventions using a health sociology approach, with social solidarity as a moderating variable to enhance community health resilience. Methods: A mixed-methods, sequential, explanatory design was used. The quantitative phase involved a cross-sectional survey of 80 respondents selected through stratified random sampling. Data were analyzed using Pearson correlation and multiple linear regression. The qualitative phase included in-depth interviews and focus group discussions with 20 key informants (community nurses, community leaders, and health officials), analyzed using thematic analysis. Results: Community strategies (β = 0.41; p < 0.001) and community nurse interventions (β = 0.45; p < 0.001) significantly influenced health resilience. Social solidarity moderated the relationship between community strategies and resilience (p < 0.05). The integrative model demonstrated strong predictive power (R² = 0.62). Qualitative findings identified four key themes: locally grounded community strategies, nurses as educators and facilitators, structural and cultural barriers, and integration as a determinant of effectiveness. Conclusion: The integration of community-based strategies and community nursing interventions significantly enhances health resilience by strengthening social solidarity, improving service access, and enabling context-based adaptation. This model provides both theoretical contributions to community health nursing and practical implications for community-based health policy in crisis settings.